1973
DOI: 10.1128/jb.114.3.1328-1335.1973
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Nature of R-Factor Deoxyribonucleic Acid Isolated from Salmonella typhimurium Minicells

Abstract: In earlier reports it was shown that a variety of extrachromosomal elements harbored in the Escherichia coli minicell producer segregate into the minicells. We show in this report that the fi+ R factor R-100-1 (derepressed derivative of R-100) similarly segregates into minicells produced by a Salmonella typhimurium strain. Four distinct classes of covalently closed circular deoxyribonucleic acid molecules are found in minicells derived from the R+ Salmonella minicell producer. The sum of the average molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In a previous paper (14), I reported a method for analyzing a plasmid, R100-1, integrated into the host chromosome by transduction to a dnaA-ts recipient. In accord with previous molecular studies in other laboratories (2,8,9,11), this plasmid was found to be a co-integrate in that it carried two independently operative replication genes, repA and repB.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In a previous paper (14), I reported a method for analyzing a plasmid, R100-1, integrated into the host chromosome by transduction to a dnaA-ts recipient. In accord with previous molecular studies in other laboratories (2,8,9,11), this plasmid was found to be a co-integrate in that it carried two independently operative replication genes, repA and repB.…”
supporting
confidence: 87%
“…This will be determined after completion of mapping of the tra cluster, which is now in progress in my laboratory. It should be noted that R100-1 has only a single gene or gene cluster responsible for incompatibility despite previous data suggesting that this plasmid is a co-integrate consisting of two replicons (2,8,9,11,14). For the classification of the conjugative plasmid by incompatibility tests to be reasonable, one plasmid, even if it is a co-integrate, should have one incompatibility gene or gene cluster specific for that plasmid.…”
Section: Resultsmentioning
confidence: 92%
“…Electron micrograph of a circular DNA molecule. Open circle, about 22 ,m, from an E. coli strain harboring plasmid pJM 3, which transfers linked resistance to sulfonamide and streptomycin.…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli, R100-1 exists almost exclusively in the form of a composite molecule. In Salmonella typhimurium, however, there is a frequent loss of the r-det component from the composite molecule (23,29,30).…”
mentioning
confidence: 99%